2022
DOI: 10.1021/acs.est.2c06814
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Interactions of Humic Acid and Minerals Reveal Mechanisms of Carbon Protection in Soil

Abstract: The concentrations of terrestrially sourced dissolved organic matter (DOM) have expanded throughout aquatic ecosystems in recent decades. Although sorption to minerals in soils is one major pathway to sequestrate soil organic matter, the mechanisms of organic matter−mineral interactions are not thoroughly understood. Here, we investigated the effect of calcium phosphate mineralization on humic acid (HA) fixation in simulated soil solutions, either with or without clay mineral montmorillonite (Mt). We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…At high concentrations, multiple binding mechanisms coexist due to the polydisperse and heterogeneous properties of HA. Therefore, it is challenging to identify the main interfacial binding mechanisms as they may occur simultaneously …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At high concentrations, multiple binding mechanisms coexist due to the polydisperse and heterogeneous properties of HA. Therefore, it is challenging to identify the main interfacial binding mechanisms as they may occur simultaneously …”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies have also found that the presence of clay minerals in soil facilitates the adsorption of CaP to DOM . Nanoparticles produced on the surface of natural clay minerals are tightly bound to the clay silicate layer, preventing them from aggregating .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The (released) labile OC as well as the liquid byproduct of hydrochar tends to form aggregates with clay minerals. 40,71,72 The refractory fraction of biochar can also form organometallic complexes with clay minerals 30,73 during aging in soil. These processes not only physically protect the newly formed aggregates/complexes from decomposition but also enhance the oxidation resistance of biochar surfaces and thus allow both refractory and labile fractions of biochar to persist in soil.…”
Section: Stability Of Biocharmentioning
confidence: 99%
“…Notably, hydrochar usually contains high levels of humic acids in its dissolved fraction, , which can account for 43.5% of the total biomass, depending on thermochemical conditions . Humic acids are widely used functional materials for soil fertility and ecological agricultural construction due to their high physiological activity, adsorption, and N-rich composition , Therefore, it is expected that the dissolved fraction of hydrochar has stronger effects on the turnover and speciation of OC than dissolved pyrochar in soil.…”
Section: Effect Of Biochar On C Cycling In Soilmentioning
confidence: 99%